Morphological Variations of Umbilical Cord in Normal Pregnancies among Local Population - Chughtai, Aneeqa; Saad Abdullah, Muhammad; Izhar, Saba; Irfan, Nida; Iftikhar, Saad; Laique, Talha (Pakistan Journal of Medical & Health Sciences, 2022)
Placenta is a unique functional center at the maternal-fetal interface. Aim: To find out the morphological variants of umbilical cord in normal pregnancies was undertaken among local population. Study design: Cross-sectional study. Methodology: Umbilical cords were collected from normal cases of delivery at Services Hospital, Lahore. Simple random sampling (probability) was done to collect hundred placentae. Grossing was done. Tissue samples were taken and processed. Histological observations were undertaken using H&E stained sections. Detailed morphology was studied to find out morphological variant with values ≤ 5%. Data was analyzed using SPSS version 20. Results: Cords that measured < 40cm in length were up to 4%. Cord with no twists was up to 1%, 1% cord with 3.5 twists, 3% cords with 4 twists, and 1% cord with 4.5 twists were present, amount of Wharton's Jelly measured to be 38.46mm2 (1%), 132.66mm2 (2%), 153.85mm2 (2%) and 176.62mm2 (4%), presence of cysts (4%), the vestigial remnants i.e. vitelline and vascular remnants 3% each and squamous metaplasia in 1% of the umbilical cord. Conclusion: Data concluded the presence of morphological variants in the umbilical cord which may reflect the developmental landmarks or other altered phenomenon during the course of pregnancy.